ANAK SEBAGAI MEDIATOR KOMUNIKASI KELUARGA DI TENGAH HUBUNGAN JARAK JAUH : (Analisis Pada Family Communication Patterns Theory) - Mutiara Pasca Nanasya; Aditya Dwi Putra Bhakti (JURNAL SIGNAL, 2026)
Communication patterns within families are often overlooked as a contributing factor to the high divorce rate, behind other internal and external factors, especially for families undergoing LDM (Long Distance Marriage). In this case, children play an important role as mediators to ensure the cohesion of migrant worker families is maintained, as occurred in Senggreng Village, Sumberpucung District, Malang Regency, which was the location of this research. During the observation, several migrant worker families were found to be able to maintain harmonious relationships despite having lived apart for almost a decade. Thus, the purpose of this study was to determine how children's strategies in mediating communication in families undergoing long-distance relationships based on communication patterns according to FCPT (Family Communication Patterns Theory). Qualitative with a phenomenological approach was used as the research method, and the research subjects were categorized into three, namely key informants, supporters, and other additional informants. Data collection techniques were carried out through four crucial stages, including In Depth Interviews, participant observation, conclusions, and data triangulation. Data analysis used the Miles & Huberman Model (1994), which consists of data reduction, data presentation, and conclusion drawing. The results of the study show that LDM (Long Distance Marriage) families in Senggreng Village successfully maintain harmony through communication patterns with a high conversation orientation in line with the Family Communication Patterns Theory perspective, and strategically manage relationships at all levels of Matouschka Dolls Theory to ensure the cohesion of migrant worker families is maintained. Children not only convey messages, but also interpret communication to maintain harmony through several strategies, such as censoring or modifying messages that contain criticism, stabilizing family emotions, and contextual bridges, which provide information to reduce the potential for misunderstanding. Although children are the key to maintaining the deepest layer of spiritual relationships despite physical separation, further research is expected to be able to further examine the influence of culture, social class, and more complex dynamics.